Model-Based Approach for Combustion Monitoring Using Real-Time Chemical Reactor Network - Pieter DePape; Igor Novosselov (Journal of Combustion)
Flame stability and pollution control are significant problems in the design and operation of any combustion system. Real-time monitoring and analysis of these phenomena require sophisticated equipment and are often incompatible with practical applications. This work explores the feasibility of model-based combustion monitoring and real-time evaluation of proximity to lean blowout (LBO). The approach uses temperature measurements, coupled with Chemical Reactor Network (CRN) model to interpret the data in real-time. The objective is to provide a computationally fast means of interpreting measurements regarding proximity to LBO. The CRN-predicted free radical concentrations and their trends and ratios are studied in each combustion zone. Flame stability and a blowout of an atmospheric pressure laboratory combustor are investigated experimentally and via a phenomenological real-time Chemical Reactor Network (CRN). The reactor is operated on low heating value fuel stream, i.e., methane diluted with nitrogen with N2/CH4 volume ratios of 2.25 and 3.0. The data show a stable flame-zone carbon monoxide (CO) level over the entire range of the fuel-air equivalence ratio (Φ), and a significant increase in hydrocarbon emissions approaching blowout. The CRN trends agree with the data: the calculated concentrations of hydroxide (OH), O-atom, and H-atom monotonically decrease with the reduction of Φ. The flame OH blowout threshold is 0.025% by volume for both fuel mixtures. The real-time CRN allows for augmentation of combustion temperature measurements with modeled free radical concentrations and monitoring of unmeasurable combustion characteristics such as pollution formation rates, combustion efficiency, and proximity to blowout. This model-based approach for process monitoring can be useful in applications where the combustion measurements are limited to temperature and optical methods, or continuous gas sampling is not practical.